The societal views for addiction recoverees’ in the UAE Society ’: A perspective study of community members’ opinions on addiction recoverees - Barhoumi, Wafa; Algharbawi, Fatima Ahmad (Al-Adab Journal, 2021)
The aim of this research was to find out how the UAE society views people who have recovered from addiction. The data was gathered using a scale with positive and negative statements based on four fundamental axes: First and foremost, how do community members react to a recovering addict in general? Second, the extent to which recovering addicts are accepted in various social communities. Third, the presence of stigma or rejection by community members when dealing with a recovering addict. And fourth, the effect of the interaction of gender and age level on the attitudes of the sample members toward recovering addicts. In addition, an in-depth interview with ten respondents from addicts who recovered and returned to Al-Amal Private Hospital for treatment or follow-up was conducted. The interviews focused on showing and demonstrating the experiences of those recovering from addiction in dealing with the external community and the extent to which it accepts them, their integration into various "social, environment, professional" aspects and their exposure to stigma and ostracism within their societies. According to recovering addicts’ narratives, the attitude of Emirati community members on recovering addicts is relatively positive, with negative indicators about "safety, trust, dealing, and integration" acting as a barrier to their integration into social capital. This result, which contradicted the respondents’ accounts and the existence of a declining social perception, regardless of age and gender, was found to be related to demographic factors (gender/age) and attitudes of Emirati community members toward recovering addicts. Furthermore, there is a significant gap between what the recovered believes from societal reality after his recovery and individual society’s perceptions and attitudes, which is a totally contradictory gap that reflects a lack of community members’ awareness in dealing properly with this recovering addict.